A redox-switchable α-cyclodextrin-based [2]rotaxane - Dichtel, William R. (2011)
A bistable [2]rotaxane comprising an alpha-cyclodextrin (alpha-CD) ring and a dumbbell component containing a redox-active tetrathiafulvalene (TTF) ring system within its rod section has been synthesized using the Cu(I)-catalyzed azide-alkyne cycloaddition, and the redox-driven movements of the alpha-CD ring between the TTF and newly formed triazole ring systems have been elucidated. Microcalorimetric titrations on model complexes suggested that the alpha-CD ring prefers to reside on the TTF rather than on the triazole ring system by at least an order of magnitude. The fact that this situation does pertain in the bistable [2]rotaxane has not only been established quantitatively by electrochemical experiments and backed up by spectroscopic and chiroptical measurements but also been confirmed semiquantitatively by the recording of numerous cyclic voltammograms which point, along with the use of redox-active chemical reagents, to a mechanism of switching that involves the oxidation of the neutral TTF ring system to either its radical cationic (TTF*+) or dicationic (TTF2+) counterparts, whereupon the alpha-CD ring, moves along the dumbbell to encircle the triazole ring system. Since redox control by both chemical and electrochemical means is reversible, the switching by the bistable [2]rotaxane can be reversed on reduction of the TTF*+ or TTF2+ back to being a neutral TTF.